Does real estate transparency matter for foreign real estate investments? - Farzanegan, Mohammad Reza; Gholipour Fereidouni, Hassan (International Journal of Strategic Property Management, 2014)
The purpose of this paper is to examine the impact of real estate transparency (RET) on foreign real estate investments (FREI). Most of the previous studies have argued that the free flow of information and the fair and consistent application of local property laws could attract greater amounts of FREI. Using observations from 32 countries covering 2004, 2006, 2008 and 2010 and applying fixed-effect and the generalized method of moments (GMM) techniques, our empirical results reveal that RET is not a major determinant of FREI. However, we find that the effect of RET on FREI is dependent on its interaction with the level of income implying that the higher the level of income in the host country, the higher the effect of RET on FREI. Finally, the results show that foreign direct investment (FDI) in other sector, market size and property prices are important determinants of FREI. First Publish Online: 8 Dec 2014